Land mobile satellite propagation characteristics from knife-edge diffraction modeling and hemispheric images - Rieche, Marie; Ihlow, Alexander; Heyn, Thomas; Pérez-Fontán, Fernando; Del Galdo, Giovanni (2015 9th European Conference on Antennas and Propagation, EuCAP 2015, 2015)
This contribution investigates the characterization of the Land Mobile Satellite (LMS) channel by estimating the path gain from Knife-Edge Diffraction (KED) modeling and hemispheric images. The geometric parameters for the KED model are derived from images of the upper hemisphere. Using geometric considerations it is possible to deduce the position of a satellite within the image. The image-based approach enables the prediction of the signal attenuation for arbitrary satellite positions. Potential error factors effecting the accuracy of the model output are investigated and discussed, e.g., the impact of the unknown path distance between the top of the obstacle and the mobile terminal. Moreover, we validate the proposed image-based KED model by comparing the result with measured power levels.
CRIS-Team Scopus Importer:2025-11-10
Keywords: Channel Modeling; Diffraction; Knife-Edge; Land Mobile Satellite; Satellite Propagation